Foreign Direct Investment and its Literature Review - Maddallah Al-Qaisi, Khaldoun (Journal of Reviews on Global Economics, 2017)
The types of investment that are made abroad are known as foreign and have majorly affected countries that engage in these activities of business. The various factors which are to be considered such as - political factor, social factor and economical factor as these factors affect the allocation of international capital. This research paper will examine and analyze the literature review which is focusing on movement of capital under foreign direct investment. Existence of a positive effect on the economy of a country that is injected with these substitutes has led to a better performance of the overall GDP and increase in national output. The same is related to economic growth. It is argued that the study based upon verified documents involves all the countries irrespective of their geographical area whereas the fact is that many of them are concerned with largest recipients of foreign direct investment such as- Asian and Latin American countries.